Acid dye biodegradation using saccharomyces cerevisiae immobilized with polyethyleneimine-treated sugarcane bagasse - Mitter, E. K. [UNESP]; Corso, C. R. [UNESP] (Springer Nature, 2013)
Chemical reagents used by the textile industry are very diverse in their composition, ranging from inorganic compounds to polymeric compounds. Strong color is the most notable characteristic of textile effluents, and a large number of processes have been employed for color removal. In recent years, attention has been directed toward various natural solid materials that are able to remove pollutants from contaminated water at low cost, such as sugarcane bagasse. Cell immobilization has emerged as an alternative that offers many advantages in the biodegradation process, including the reuse of immobilized cells and high mechanical strength, which enables metabolic processes to occur under adverse conditions of pH, sterility, and agitation. Support treatment also increases the number of charges on the surface, thereby facilitating cell immobilization processes through adsorption and ionic bonds. Polyethyleneimine (PEI) is a polycationic compound known to have a positive effect on enzyme activity and stability. The aim of the present study was to investigate a low-cost alternative for the biodegradation and bioremediation of textile dyes, analyzing Saccharomyces cerevisiae immobilization in activated bagasse for the promotion of Acid Black 48 dye biodegradation in an aqueous solution. A 1 % concentration of a S. cerevisiae suspension was evaluated to determine cell immobilization rates. Once immobilization was established, biodegradation assays with free and immobilized yeast in PEI-treated sugarcane bagasse were evaluated for 240 h using UV-vis spectrophotometry. The analysis revealed significant relative absorbance values, indicating the occurrence of biodegradation in both treatments. Therefore, S. cerevisiae immobilized in sugarcane bagasse is very attractive for use in biodegradation processes for the treatment of textile effluents. © 2012 Springer Science+Business Media Dordrecht.
Keywords: Acid Black 48; Biodegradation; Immobilization; Saccharomyces cerevisiae; Sugarcane bagasse; Textile dyes; Acid dye; Biodegradation process; Chemical reagents; Contaminated water; High mechanical strength; Immobilization process; Immobilization rates; Immobilized cells; Immobilized yeasts; Ionic bonds; Low costs; Metabolic process; Polyethyleneimine; Polymeric compounds; Relative absorbance; S.cerevisiae; Solid material; Sugar-cane bagasse; Textile effluent; UV-vis spectrophotometry; Adsorption; Bagasse; Bioremediation; Cell immobilization; Inorganic compounds; Microbiology; Radioactive waste vitrification; Suspensions (fluids); Textile industry; Textiles; Water pollution; Yeast; bagasse; dye; polyethyleneimine; biodegradation; color; effluent; immobilization; aqueous solution; bioremediation; biosorption; controlled study; immobilized cell; nonhuman; sugarcane